2015
DOI: 10.3221/igf-esis.35.26
|View full text |Cite
|
Sign up to set email alerts
|

Crack growth threshold under hold time conditions in DA Inconel 718 – A transition in the crack growth mechanism

Abstract: Aeroengine manufacturers have to demonstrate that critical components such as turbine disks, made of DA Inconel 718, meet the certification requirements in term of fatigue crack growth. In order to be more representative of the in service loading conditions, crack growth under hold time conditions is studied. Modelling crack growth under these conditions is challenging due to the combined effect of fatigue, creep and environment. Under these conditions, established models are often conservative but the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Reducing the loading frequency also leads to increased CGRs. At high temperature, under hold-time conditions, increased CGRs are accompanied with intergranular fracture while transgranular fracture is usually observed under pure fatigue loading, or under hold-time conditions in the near-threshold regime [11].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the loading frequency also leads to increased CGRs. At high temperature, under hold-time conditions, increased CGRs are accompanied with intergranular fracture while transgranular fracture is usually observed under pure fatigue loading, or under hold-time conditions in the near-threshold regime [11].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the fatigue-crack growth rate of an alloy increases with the increase of hold-time, because of the effects of creep and oxidation. Consequently, the creep damage at the grain boundary is aggravated and the embrittlement phenomenon caused by oxidation occurs, that accelerate the expansion of cracks [ 26 , 27 ]. However, it was found that the acting time of creep had a significant effect on the fatigue-crack growth rate in 718Plus alloy ( Figure 4 ), especially in the low stress intensity factor range (Δ K ).…”
Section: Resultsmentioning
confidence: 99%